Size Selectivity of Anionic and Cationic Dyes Using LDH Modified Adsorbent with Low-Cost Rambutan Peel to Hydrochar - Normah Normah; Novie Juleanti; Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Neza Rahayu Palapa; Tarmizi Taher; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Modification of the layered double hydroxide of CuAl-LDHs by composite with hydrochar (HC) to form CuAl-HC LDH. Material characterization by XRD, FT-IR and SEM analysis was used to prove the success of the modification. The characterization of XRD and FT-IR spectra showed similarities to pure LDH and HC. Selectivity experiments were carried out by mixing malachite green, methylene blue, rhodamine-B, methyl orange, and methyl red to produce the most suitable methyl blue dye for CuAl-LDH, HC and CuAl-HC adsorbents. The effectiveness of CuAl-HC LDH as adsorbent on methylene blue adsorption was tested through several influences such as adsorption isotherm, thermodynamics, and adsorbent regeneration. CuAl-HC LDH adsorption isotherm data shows that the adsorption process tends to follow the Langmuir isotherm model with a maximum adsorption capacity of 175.439 mg/g with a threefold increase compared to pure LDH. The effectiveness of the adsorbent for repeated use reaches five cycles as evidenced by the maximum capacity regeneration data reaching 82.2%, 79.3%, 77.9%, 76.1%, and 75.8%. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).